Mechanisation of agriculture work in Sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Mechanisation of agriculture work in Sub-Saharan Africa: Proposal for integration of mechanisation in sustainable rural development strategies